الضوابط القانونية لممارسة حق الإضراب في التشريع الوظيفي الجزائري - أسماء، قاضي; أمال ،بن حرز الله; سميرة، طليبة (جامعة الوادي University of El Oued, 2024)
ممارسة الإضراب قد يمس بعدة مبادئ قانونية هامة في مجال القانون الإداري ومن أهمها مبدأ سير المرافق العامة بانتظام واضطراد، لذا حاول المشرع الجزائري من خلال العديد من القوانين وصولا إلى أخر قانون رقم 23-08 المتعلق بالوقاية من النزاعات الجماعية في العمل وتسويتها وممارسة حق الإضراب إيجاد إطار قانوني منظم لممارسة هذا الحق دون تعسف من طرف الإدارة المستخدمة من خلال حماية العلاقة الوظيفية كضمانة للموظف العمومي مع ضمان حسن استمرارية سير المرفق العام، وجعل قيودا تحدد ممارسته وفق إطار قانوني يجعل اللجوء إليه في قطاع الوظيفة العمومية من الحقوق المكفولة قانونيا. The practice of a strike may affect several important legal principles in the field of administrative law, the most important of which is the principle of the regular and regular operation of public facilities. Therefore, the Algerian legislator tried, through many laws, up to the latest Law No. 23-08 related to the prevention and settlement of collective disputes at work, and the exercise of the right to strike, to find A legal framework regulates the exercise of this right without arbitrariness by the employing administration by protecting the employment relationship as a guarantee for the public employee while ensuring the good continuity of the functioning of the public facility, and creating restrictions that determine its exercise in accordance with a legal framework that makes resorting to it in the public service sector one of the legally guaranteed rights
ماستر اداري